Contribution of agricultural cooperatives to territorial development in Uruguay - Rodriguez Miranda, Adrian; Martí, Juan Pablo; Rodríguez Vivas, Mariana (Cooperativismo & Desarrollo, 2021)
The aim of the article is to analyze the relationship between agricultural cooperativism and territorial development in Uruguay. First, the theoretical bases of the territorial development approach are presented, highlighting the coincidences with cooperativism. From this, the category of endogenous development is proposed as the main link between the two approaches. The methodology consists of a descriptive and exploratory analysis, with a historical focus, based on a bibliographic and documentary review, secondary information and interviews with key actors. To obtain the results, the history and evolution of cooperativism in Uruguay is analyzed, and then it focuses on agricultural cooperativism, its origins, its most representative cases and its evolution. The results show a positive contribution of agricultural cooperatives to territorial development, supported on an important role of public policies. Cooperatives promotes the competitiveness of the territory in international markets, but protects the local productive systems of small producers from the logic of concentration and exclusion of transnational capital. In turn, cooperatives favor endogenous capacities for innovation and the construction of local social capital and networks that are the basis of local development strategies.